Ethics of abortion in transplantation - Ramos, Hector C; Hill, Allison (Current opinion in organ transplantation, 2024)
The controversial medical procedure of abortion is the subject of this article. It argues that for transplant patients, including recipients, abortion is ethical. In June 2022, the United States Supreme Court overturned the long-standing decision of Roe v. Wade. This decision has led to a socio-legal environment where obtaining an abortion is impossible for some patients. However, the moral position relating to patients who have undergone transplants or are on a waiting list has been largely overlooked. End-stage renal, liver, and heart disease presents a hazardous situation for pregnancy, posing risks to both the fetus and the pregnant person. The abortion procedure is medically safer and allows a patient to proceed with a transplant. Limiting access to abortion or preventing it altogether will have a significant negative impact on transplant patients. The ethical analysis of abortion can be likened to compelling a relative or loved one of a transplant recipient to donate an organ to their family member or loved one. This article emphasizes the importance of maintaining the legal availability of abortion for transplant patients. Allowing abortions in transplant patients upholds ethical parity, as seen in the analogous situation of live organ donation.